A Decision-Making Model for Industrial Development - Saunders, M.J. (My University, 1973)
Studies of industrial location decision-making and the construction of decision-making models to date have invariably been couched in behavioural terms.1 Likewise the majority, if not all of such empirical studies have centred on the industrialist as the decision- maker, on the assumption that, because he has made a location decision, he necessarily knows how best to do so. Little or no attention has been paid to the legislative structures within which industrial location decisions must be made, or to the part played by the elected representatives who are responsible for making such decisions. This paper is an attempt to escape from the behavioural habit by developing a structural model for industrial location and development decision-making at the community level.
Title: A Decision-Making Model for Industrial Development, Author: M. J. Saunders, Location: Thode